Misoprostol for prevention and treatment of postpartum haemorrhage: A systematic review - Kabelo M. Olefile; Oswell Khondowe; Doreen M'Rithaa (AOSIS, 2013)
Background: Postpartum haemorrhage (PPH) is a leading cause of maternal mortality especially in the developing world. Misoprostol, a highly effective drug is highly effective in inducing uterine contractions and has been proposed as a low-cost, easy-to-use intervention for PPH. Objective: This study assessed evidence of the effectiveness of misoprostol for the prevention and treatment of PPH. Method: Databases searched included MEDLINE, PUBMED, CINHAL, Google Scholar, Cochrane Central Register of Controlled Trials (CENTRAL) and EMBASE. Reference lists and conference proceedings were also searched for more studies. Three studies included in the meta-analysis were limited to randomised controlled trials (RCT). Two reviewers independently screened all articles for methodological quality using a standardised instrument adapted from the Cochrane Collaboration website. Data were entered in Review Manager 5.1 software for analysis. Results: Three trials (n = 2346) compared misoprostol to a placebo. Misoprostol was shown not to be effective in reducing PPH (risk ratios [RR] 0.65; 95% confidence interval [CI] 0.40-1.06). Only one trial reported on the need for a blood transfusion (RR 0.14; 95% CI 0.02-1.15). Shivering (RR 2.75; 95% CI 2.26-3.34) and pyrexia (RR 5.34; 95% CI 2.86-9.96) were significantly more common with misoprostol than with a placebo. Conclusion: The use of misoprostol was not associated with any significant reduction in the incidence of PPH. Therefore, in order to verify the efficacious use of misoprostol in the treatment of PPH, specialised investigations of its dose and routes of administration for clinically significant effects and acceptable side effects are warranted.